2014
DOI: 10.3109/10428194.2014.905772
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive mature natural killer cell neoplasms: report on a series of 12 European patients with emphasis on flow cytometry based immunophenotype and DNA content of neoplastic natural killer cells

Abstract: We report 12 cases of aggressive natural killer (NK) cell neoplasms diagnosed in Portugal, with emphasis on flow cytometry. Ten patients had extranodal NK/T cell lymphoma, nasal type and two had aggressive NK cell leukemia, and seven were men and five were women, with a median age of 50 years. NK cells brightly expressed the CD56 adhesion molecule and CD94 lectin type killer receptor and had an activation-related HLA-DR+ CD45RA+ CD45RO+ immunophenotype, in most cases. In contrast, dim CD16 expression was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…1 The immunophenotype of aggressive NK-cell leukemia/lymphoma is suggestive of a neoplastic counterpart of a normal NK cell that has undergone activation and transformation after EBV infection. 17,18 Evidence of EBV infection is a key diagnostic feature of aggressive NK-cell leukemia/lymphoma. EBVnegative aggressive NK-cell leukemia/lymphoma is rare and its clinicopathological features are not well recognized.…”
Section: Next-generation Sequencingmentioning
confidence: 99%
“…1 The immunophenotype of aggressive NK-cell leukemia/lymphoma is suggestive of a neoplastic counterpart of a normal NK cell that has undergone activation and transformation after EBV infection. 17,18 Evidence of EBV infection is a key diagnostic feature of aggressive NK-cell leukemia/lymphoma. EBVnegative aggressive NK-cell leukemia/lymphoma is rare and its clinicopathological features are not well recognized.…”
Section: Next-generation Sequencingmentioning
confidence: 99%
“…Immunophenotypically, although they are cell surface CD3 (sCD3)‐negative and CD2‐positive, the published data regarding these rare entities suggest that they can be very different in other surface antigen expression. ANKL is thought to usually exhibit a CD56+/CD16−/CD57− phenotype , whereas CLPDNK shows a CD56−/CD16+/CD57+ phenotype . Here, we report an unusual case of NK‐cell neoplasm having an immunophenotype similar to that associated with ANKL but with clinical and laboratory features typical of the much more indolent CLPDNK.…”
Section: Introductionmentioning
confidence: 79%
“…Much of the previous data regarding the phenotype of ANKL are generated from immunohistochemical studies, which limits their utility in regards to comparison to flow cytometry . Recently, comprehensive flow cytometric immunophenotyping studies for ANKL from a Japanese group of 22 cases , European group of 12 cases , and a Chinese group of 29 cases revealed that all cases have bright CD56 expression and lack CD57 expression. The vast majority of cases do not express CD16 or CD8 , although some cases are CD16 positive .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting flow cytometric studies can assist by distinguishing T‐cell LGLL, usually CD2+, CD3+, CD5+(dim), CD7+(dim), CD8+, CD16+, CD57+, from a chronic lymphoproliferative disorder of NK‐cell, usually CD2+, CD3(−), CD5(−), CD16+(dim/bright), CD56+/−, CD57(−) . In addition, flow cytometric studies can help to distinguish LGLL from more aggressive neoplasms, such as aggressive NK‐cell leukemia (Figure ).…”
Section: Complete Blood Cell Count and Peripheral Smear Review Findingsmentioning
confidence: 99%